LearnLynk: Empowering the Next Generation of Learners - Asoke Nath,; Bijetree Basak,; Sania Rahaman,; Tanushree Jati, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The COVID-19 crisis initiated the extensive use of online learning in the education sector, making it imperative for a new, purpose-built learning management system. Platforms like Microsoft Teams and Zoom were originally created for the business environment, with platforms like Google Classroom offering school work with limited real-time communication. They tended to miss the mark when it comes to productivity, interactivity, and improved learning experience. The present work looks at such disadvantages and presents a new approach to learning management systems, designed for the education sector. It seeks to develop a safe and easy-to-use platform for the teachers and the learners to make their online teaching-learning experience more efficient, resulting in improved learning outcomes in the virtual world.
Keywords: Learning Management System (LMS); Django; Virtual learning